Miscelleneous
Its a collection of a variety of bibliographies on avariety of topic s which include among other higher education, complete bibliography of Makerere University publications, bibliography of Ugandan bibliographie s.
AR/SIC/1/3
English
Shelf no. 3
Keywords: Bibliography